2017
DOI: 10.1111/ter.12254
|View full text |Cite
|
Sign up to set email alerts
|

The supergene origin of ruthenian hexaferrum in Ni‐laterites

Abstract: For two decades, the nature of Fe-rich, oxygen-bearing, Ru-Os compounds found in the supergene environment has been debated. Ru-Os-Fe-oxides and nano-intergrowths of ruthenium with magnetite have been proposed. We applied FE-SEM, EMPA, l-Raman spectroscopy and synchrotron tts-lXRD to Ru-Os-Fe compounds recovered from Ni-laterites from the Dominican Republic. The results demonstrate that a significant portion of Fe exists in a common structure with the Ru-Os alloy, that is, ruthenian hexaferrum. This mineral oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 29 publications
0
18
1
Order By: Relevance
“…The observation of subsequent Fe-incorporation into secondary Ru-Os-Ir alloys via abiotic and/or biological processes has been used as an evidence for a supergene origin of ruthenian hexaferrum found in Ni-laterites from the Dominican Republic [20]. Here, the presented XRD data of one characteristic fibrous PGM with an isometric morphology suggest that such a PGM transformation from primary laurite toward ruthenian hexaferrum has occurred ( Figure 3A; Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The observation of subsequent Fe-incorporation into secondary Ru-Os-Ir alloys via abiotic and/or biological processes has been used as an evidence for a supergene origin of ruthenian hexaferrum found in Ni-laterites from the Dominican Republic [20]. Here, the presented XRD data of one characteristic fibrous PGM with an isometric morphology suggest that such a PGM transformation from primary laurite toward ruthenian hexaferrum has occurred ( Figure 3A; Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 81%
“…A comparison with literature data for chemically related mineral phases (Os-group minerals) revealed that the fibrous PGM has rather identical X-ray line intensities and observed d-spacings as ruthenian hexaferrum [20] (Table 1). On this basis, the X-ray powder pattern for the fibrous PGM was indexed, leading to the refined unit-cell dimensions: a 2.6670 (13) Å, c 4.2361 (18) Å, V: 26.095 (27) Å 3 , Z = 2 ( Table 2).…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 84%
See 2 more Smart Citations
“…More recently, there have been a number of studies by Joaquín Proenza and his group at the University of Barcelona on the Loma Peguera and Loma Larga chromitites, in the central part of Loma Caribe peridotite, Cordillera Central of the Dominican Republic (e.g. Proenza et al , 2008; McDonald et al , 2010, Aiglsperger et al , 2017 a , b ). The ultramafic rocks consist mostly of harzburgite, dominantly clinopyroxene-rich harzburgite (modal content up to 5% Cpx) with small amounts of dunite and lherzolite, considered to represent the mantle sequence of an ophiolite (Lewis and Jimenez, 1991; Lewis et al , 2006; Marchesi et al , 2016) and have been heavily serpentinized with a well-developed nickel-rich laterite having formed over them.…”
Section: Introductionmentioning
confidence: 99%